STRUCTURAL FORMATION OF LEXICAL UNITS RELATED TO CALLIGRAPHY (American Journal of Pedagogical and Educational Research, 2026)
The article analyzes the morphological and semantic formation of lexical units related to the art of calligraphy, the transformation of terms borrowed from Arabic and Persian into the Uzbek language, and their role in the cultural context. The research is conducted in accordance with IMRAD requirements, and calligraphy terms are extensively studied based on historical sources, dictionaries, and modern linguistic theories.